On considering the application of Amartya Sen’s capability approach to analyze the well-being of Hindu clergy in Bali - A.A K Ayuningsasi; M.K S Budhi; I.N M Yasa; A.A I.N Marhaeni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This paper aims to determine the possibility of applying Amartya Sen’s Capability Approach to analyze the well-being of Hindu clergy in Bali. Literature studies were carried out on the variables mentioned by Amartya Sen in several of his writings and studies, as well as studies conducted by several economists as a further study of Sen's theory. This study offers a conceptual framework to explain and predict the influence of variables in Sen's theory on the achievement of the well-being of Hindu clergy in Bali. The variables studied in this paper are resources, commodities, capabilities, conversion factors, social choice, and functioning. In this case, commodities and capabilities can act as mediating variables, while conversion factors and social choice are considered to moderate the influence of resources on the achievement of functioning.